How does stigma affect people with psoriasis? - Łakuta, Patryk; Marcinkiewicz, Kamil; Bergler-Czop, Beata; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Psoriasis is associated with a major additional psychological burden. Aim : To investigate whether the extent of skin involvement, stigmatization, and perceived social support are related to depressive symptoms in psoriasis patients. Material and methods: One hundred and forty-eight psoriasis patients completed in the BSA, the Beck Depression Inventory, Stigmatization Scale, and Multidimensional Scale of Perceived Social Support. Results: Almost 13% of participants obtained a BDI total score indicating moderate depressive symptoms. The results of regression analysis revealed that greater depression severity in psoriasis patients is associated with higher levels of psoriasis-related stigma, lower perceived social support, female gender and a shorter duration of the disease, explaining 43% of the variance of depression. The stigmatization was the most powerful predictor of depressive symptoms for psoriasis patients and accounted for 33% of the variance. Conclusions : The extent of psoriasis does not directly lead to mood disturbance in these patients. Rather, social stigma accounted for this relationship. Strategies for reducing the stigma attached to patients with psoriasis are required.